1996
DOI: 10.1901/jeab.1996.65-57
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent‐schedule Performance in Dairy Cows: Persistent Undermatching

Abstract: Performance of dairy cows responding under concurrent variable-interval variable-interval schedules of food delivery was examined, with results analyzed in terms of the generalized matching equation. In Experiment 1, bias measures indicated that crushed barley was preferred over meatmeal when these foods were available under the alternative schedules. For whole-session data, substantial undermatching of response and time-allocation ratios to obtained reinforcement ratios was evident. Postreinforcement pause ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Perhaps species differences or some aspect of the behavioral situation contributed to the relatively lower slopes seen in the present study. However, slopes consistently below 0.6 for both time and response allocation have been reported (e.g., Foster et al 1996). In some experiments, undermatching has been found to increase as the number of successive conditions presented to the same subjects increased (Keller and Gollub 1977;Todorov et al 1983), a factor that could have contributed to the present results.…”
Section: Discussionsupporting
confidence: 51%
“…Perhaps species differences or some aspect of the behavioral situation contributed to the relatively lower slopes seen in the present study. However, slopes consistently below 0.6 for both time and response allocation have been reported (e.g., Foster et al 1996). In some experiments, undermatching has been found to increase as the number of successive conditions presented to the same subjects increased (Keller and Gollub 1977;Todorov et al 1983), a factor that could have contributed to the present results.…”
Section: Discussionsupporting
confidence: 51%
“…Red Green Hen 11 13 14 15 11 13 14 15 11 13 14 15 11 13 14 15 11 13 14 15 11 13 14 15 11 13 14 15 11 13 14 15 11 13 14 15 11 13 14 15 11 13 14 15 11 13 (Foster, Temple, Robertson, Nair, & Poling, 1996), much bigger than that reported for cows' preferences for crushed barley over dairymeal (Matthews & Temple, * 1979), and less than that reported for pi-!8 geons' preferences for wheat over electrical stimulation of the brain (Hollard & Davison, 1971). In the studies just cited, measures of bias from response and time data were very similar.…”
Section: VImentioning
confidence: 99%
“…The study results strongly indicated that cows can distinguish color. Further use of operant conditioning was seen in a study that determined cow food preferences where cows were given a choice between food reinforcement opportunities (23,24) . The results of the study indicated that cows preferred crushed barley to meatmeal showing that operant conditioning and positive reinforcement can be used to learn more about cattle preferences, learning, and discrimination.…”
Section: Cowsmentioning
confidence: 99%